The Impact of Disclosing Sponsored Marketing to Children: A Pilot Randomized Controlled Trial - Wannapaschaiyong, Prakasit; Saleepatcharaporn, Kamolchanok; Rojmahamongkol, Pat (Ramathibodi Medical Journal, 2025)
Background:Early primary school children (ages 6-8 years) often struggle to recognize advertising content and understand its persuasive intent, particularly in digital media. With increasing exposure to sponsored content on platforms, such as YouTube, there is a critical need for effective methods to enhance children’s advertising literacy. Objective: To evaluate the impact of child-specific advertising disclosure on advertising literacy among children aged 6 to 8 years. Methods: This pilot randomized controlled trial, 43 primary school children in Thailand were randomly assigned to control or intervention groups. The intervention group viewed a 10-second disclosure stating, “This person received money to use the product in this content,” before watching a mock YouTube unboxing video. Advertising literacy was assessed via questionnaires at baseline, immediately postintervention, and at 3-month follow-up. Results: Among 43 participants (51.6% female, mean age 7.31 years), the control group demonstrated a significant decrease in overall advertising literacy scores from pretest to posttest (P = .049), driven by reduced brand recognition, source recognition, and understanding of selling intent. In contrast, the intervention group maintained their advertising literacy (P = .110), with a stable understanding of persuasive intent and a trend toward improved understanding of selling intent. Scores remained consistent from the posttest to 3-month follow-up in both groups. Conclusions: Child-inspired advertising disclosure prevented a decline in advertising literacy, particularly for persuasive and selling intent components. These findings suggest that customized disclosures may enhance young children’s recognition of advertising commercial motives.